Efektivitas Nebulisasi Budesonide dalam Menurunkan Derajat Sesak pada Pasien Bronkopneumonia Akut - Dinda Hasianty Nababan; Maria Astrid (Lontara Journal of Health Science and Technology, 2026)
Acute bronchopneumonia is a major cause of respiratory distress in children, often requiring immediate emergency care. This condition is characterized by airway inflammation and increased secretion production, which can exacerbate shortness of breath. This study aimed to analyze the effectiveness of nebulization therapy using budesonide on changes in the degree of shortness of breath in patients with acute bronchopneumonia. This study used a case study approach with the application of the nursing process to pediatric patients treated in the emergency department. Data were collected through clinical assessment, observation of respiratory signs, supporting examination results, and evaluation of patient responses before and after nebulization intervention. The results showed clinical improvement characterized by decreased respiratory rate, reduced chest retractions, and increased breathing comfort after nebulization of budesonide. These findings suggest that nebulization of budesonide has the potential to be an effective supportive intervention in helping improve respiratory status in patients with acute bronchopneumonia.